311 Multi-institutional Analysis on Rate of Pseudarthrosis Following Anterior Cervical Discectomy and Fusion Using Allograft Cellular Bone Matrix (Osteocel). (1st March 2022) - Wang, Timothy Y.; Bergin, Stephen M.; Park, Christine; Rajkumar, Shashank; Goodwin, C. Rory; Karikari, Isaac O.; Abd-El-Barr, Muhammad; Shaffrey, Christopher I.; Yarbrough, Chester; Than, Khoi D.
Abstract : INTRODUCTION: Usage of osteobiologics is becoming increasingly common for spinal fusion procedures, but the efficacy of certain products is unclear. METHODS: The medical record across three medical centers and seven spine surgeons was retrospectively queried for patients undergoing single-level ACDF utilizing Osteocel. Pseudarthrosis was determined based on computed tomography (CT) or x-rays of the cervical spine. Patients were determined to have radiographic pseudarthrosis if they met any of the following criteria: 1) lack of bridging bone on CT obtained >300 days postoperatively, 2) evidence of instrumentation failure, or 3) motion across index level as seen on flexion/extension cervical spine x-rays. Univariate and multivariate analyses were then performed to identify independent preoperative or perioperative predictors of pseudarthrosis in this population. RESULTS: A total of 326 patients met inclusion criteria. Forty-three (13.2%) patients met criteria for pseudarthrosis, of which 15 underwent revision surgery (34.9%). Age (54.1 vs 53.8 years), sex (34.9% vs 47.4% male), race, prior cervical spine surgery (37.2% vs 33.6%), tobacco abuse (16.3% vs 14.5%), chronic kidney disease (2.3% vs 2.8%), and diabetes (18.6% vs 14.5%) were not significantly different between patients with or without pseudarthrosis, respectively (p > 0.05). Presence of osteoporosis (16.3% vs 3.5%) was associated with pseudarthrosis (p < 0.001). Implant-type was also significantly associated with pseudarthrosis, with a 16.4% rate of pseudarthrosis for patients with polyetherethereketone (PEEK) implants versus 8.4% for patients with allograft implant (p = 0.04). Average length of follow-up was 27.6 and 23.8 months for patients with and without pseudarthrosis, respectively. Multivariate analysis demonstrated osteoporosis (OR: 4.97, 95% CI [1.51-16.4], p < 0.01) and usage of PEEK implant (OR: 2.24, 95% CI [1.04-4.83], p = 0.04) as independent predictors of pseudarthrosis. CONCLUSION: The usage of Osteocel in single-level ACDF is associated with a higher rate of pseudarthrosis compared to the literature-reported fusion rates for alternative osteobiologics. This is especially true when Osteocel is combined with a PEEK implant.